Early Differentiation of Human CD11c+NK Cells with γδ T Cell Activation Properties Is Promoted by Dialyzable Leukocyte Extracts. (25th October 2016) - Ramírez-Ramírez, Dalia; Vadillo, Eduardo; Arriaga-Pizano, Lourdes Andrea; Mayani, Héctor; Estrada-Parra, Sergio; Velasco-Velázquez, Marco Antonio; Pérez-Tapia, Sonia Mayra; Pelayo, Rosana
Abstract : Reconstitution of the hematopoietic system during immune responses and immunological and neoplastic diseases or upon transplantation depends on the emergent differentiation of hematopoietic stem/progenitor cells within the bone marrow. Although in the last decade the use of dialyzable leukocyte extracts (DLE) as supportive therapy in both infectious and malignant settings has increased, its activity on the earliest stages of human hematopoietic development remains poorly understood. Here, we have examined the ability of DLE to promote replenishment of functional lymphoid lineages from CD34 + cells. Our findings suggest that DLE increases their differentiation toward a conspicuous CD56 + CD16 + CD11c + NK-like cell population endowed with properties such as IFNy production, tumor cell cytotoxicity, and the capability of inducing γδ T lymphocyte proliferation. Of note, long-term coculture controlled systems showed the bystander effect of DLE-stromal cells by providing NK progenitors with signals to overproduce this cell subset. Thus, by direct effect on progenitor cells and through activation and remodeling of the supporting hematopoietic microenvironment, DLE may contribute a robust innate immune response by promoting the emerging lymphopoiesis of functional CD11c + NK cells in a partially TLR-related manner. Unraveling the identity and mechanisms of the involved DLE components may be fundamental to advance the NK cell-based therapy field.